Perencanaan Sistem Penyediaan Air Minum (SPAM) Pedesaan Dusun IV Desa Sumberejo Kabupaten Tanggamus - Dwi May Juwita; Repinka Cornelia; Aqmal Satrio Dirgantara; Suprapto Suprapto; Ismadi Raharjo (Jurusan Teknologi Pertanian, 2014)
Fresh water is a basic need for human, so is Â to be normal if the water sector gets priority in the handling and fulfillment. The springs are located in DusunÂ Sumberejo IV should be able to meet the water needs of the local community. The purpose of this study was: (1) identify potential sources of raw water (water) in Dususn Sumberejo IV, (2) calculate the number of people that will be served as well as the need for clean water, (3) designing the layout and capacity of the reservoir, (4) determine the appropriate piping standards for Rural Fresh Water Supply System (SPAM), and (5) predict the draft budget piping. The method used is the discharge measurements, measurements of topography, socio-economic survey, the calculation of water requirements, head loss effective calculation and Budget Plan (RAB), whereas for hidraulic analysis using Epanet program. Results of fresh water supply planning is done for rural population projections to 2020 the number of 491 people, need for fresh water in the Dusun Sumberejo IV 0.32 liters/sec, discharge available in the spring Sumberejo is 0.35 liters/second then the discharge is still sufficient for the water needs until the year 2020. From the measurement results obtained topographic maps + 50.42 m height difference by elevation above sea level on the Bench Mark (a point of reference, the location of the source of raw water springs) + 446 m above sea level and at the end point measurement (area of service farthest) +399.57 m above sea level, so the system can distribuasi to the service area using gravity. The results of the hydraulic analysis using EPANET used PVC pipes with various diameters ranging from 12.5 to 50 mm with a length of 4876 meters and its accessories (accessories). Based on these forecasts Rural SPAM development requires an investment of around Rp. 89,000,000.00, then the system when the service is expected to last for 25 years as well as in the development of investment in the form of loans with mortgage interest (soft loans) amounted to 6% of the obtained water price per m3 in Dususn IV Sumberejo IV Â around Rp. 1450.00/m3. Keywords: rural SPAM, gravitasi system EPANET